Analisa Ketersediaan Air pada Embung di Desa Hegarmanah Kabupaten Cianjur - Azka Mutsla Fauzan; Sulwan Permana (Jurnal Konstruksi, 2025)
Cianjur Regency has hydrological potential in the form of rivers and beaches. However, there is still a problem of water shortage. One of the areas experiencing this problem is the Karangtengah Subdistrict area in Hegarmanah Village. When the dry season arrives, the available water is not able to meet the needs of the community. Hegarmanah Village itself has a water source from the river and actually already has a clean water network. However, the clean water network is not functioning due to pumping and water availability issues. To overcome the availability of water in the area, it is necessary to build a facility, namely embung. Embung Hegarmanah is an embung built in Cianjur Regency, precisely in Hegarmanah Village. The research conducted this time, calculating the amount of water availability and needs to meet the irrigation needs of Hegarmanah embung. The method used in this research is quantitative method. In finding the amount of water availability and needs, it is necessary to calculate the incoming discharge and outgoing discharge at Embung Hegarmanah. The results of this study found that there was a water shortage in August of 104.3 l / s, with a land area of 32.52 Ha. Water shortages occur because in August the rainfall is low and farmers are processing crops for the planting period.